Interactions of the cell-wall glycopolymers of lactic acid bacteria with their bacteriophages - Chapot-Chartier, Marie-Pierre (Frontiers in Microbiology, 2014)
Lactic acid bacteria (LAB) are Gram positive bacteria widely used in the production of fermented food in particular cheese and yoghurts. Bacteriophage infections during fermentation processes have been for many years a major industrial concern and have stimulated numerous research efforts. Better understanding of the molecular mechanisms of bacteriophage interactions with their host bacteria is required for the development of efficient strategies to fight against infections. The bacterial cell wall plays key roles in these interactions. First, bacteriophages must adsorb at the bacterial surface through specific interactions with receptors that are cell wall components. At next step, phages must overcome the barrier constituted by cell wall peptidoglycan to inject DNA inside bacterial cell. Also at the end of the infection cycle, phages synthesize endolysins able to hydrolyze peptidoglycan and lyse bacterial cells to release phage progeny. In the last decade, concomitant development of genomics and structural analysis of cell wall components allowed considerable advances in the knowledge of their structure and function in several model LAB. Here, we describe the present knowledge on the structure of the cell wall glycopolymers of the best characterized LAB emphasizing their structural variations and we present the available data regarding their role in bacteria-phage specific interactions at the different steps of the infection cycle.